Patellar denervation for Anterior Knee Pain Management in Knee Arthroplasty - Sadigursky,David (2017)
OBJECTIVE: To compare the effectiveness of patellar denervation versus non-patellar denervation in reducing anterior knee pain on a follow-up period of at least one year after total knee arthroplasty. METHOD: Data from 84 patients, who underwent total knee arthroplasty were analyzed. Participants were divided into 2 groups; group A: 42 patients who previously underwent total knee arthroplasty with patellar denervation; and group B: 42 patients who previously underwent total knee arthroplasty without patellar denervation. Results were evaluated using WOMAC and KSS questionnaires, and the VAS pain measurement. Knee ranges of motion were measured. Preoperative clinical conditions of both groups were similar. RESULTS: Postoperatively, the following results were observed. (a), the WOMAC scores for group A were significant better when compared to group B (27.95 ± 5.89 vs. 33,55 ± 6.23; (b) better results were also found in KSS scores for group A vs. group B (86.19 ± 7.10 vs. 83,07 ± 4.88); (c) the range of knee flexion was smaller than in group A vs. group B (119.0 ± 10.7 vs 125.5 ± 11.0 degrees); (d) there was no significant difference between the mean of range of knee extension between the two groups groups; (e) in terms pain referred by the patient, no difference was observed according to VAS pain. CONCLUSION: Patellar denervation does not show better effect in pain reduction compared with TKA with non-patellar denervation. However, it had a better beneficial effect on knee function score, as measured through the KSS and WOMAC questionnaires.